Relação entre a qualidade ambiental de mananciais de abastecimento da região sul-metropolitana de Goiânia e sua comunidade de macroinvertebrados aquáticos - Teixeira, André Luiz (2015)
Most of the water used to supply comes from surface sources (rivers, streams and lakes) human suffering severe pressure and, in consequence, has undergone significant changes in its quality. Human activities, among them the removal of permanent preservation areas, as riparian forests, has facilitated the process of silting and leaching of contaminants, jeopardizing water quality for both the maintenance of aquatic ecological processes and their communities, and for the supply human. In this sense, the main objective of this study was to evaluate the water quality of four watersheds stretches located in the metropolitan area south of Goiania, in the cities of Abadia de Goiás, Aparecida de Goiania, Aragoiania and Senador Canedo, which are used for public supply by means of macroinvertebrate community. The environmental integrity was assessed by means of a rapid assessment protocol of the diversity of habitats, the physicochemical parameters of the water to the community of aquatic macroinvertebrates correlated, we used a Benthic Multimetric index for classification of water bodies . It was also used ecological metrics of the sampled aquatic macroinvertebrates such as wealth index, abundance, diversity and evenness, comparing the sampling points and existing micro-habitats. It was also verified the influence of seasonality in these indices as well as the trophic structure of the community. The results of the ecological conditions made through rapid assessment protocol of habitat diversity indicated that all watersheds studied in this work are suffering or have suffered from human impacts from agricultural activities and environments were considered abnormal. Regarding the macroinvertebrate communities, the sources generally showed diversity values similar and considerably high. The cities studied have relatively similar supply sources in both microhabitats as in land use. Despite the problems that exist in regions such as livestock in inappropriate areas, the index analyzing aquatic macroinvertebrates, states that the water quality is good, both for the high presence of sensitive taxa to distrúrbio, as the low abundance of taxa indicators low quality. The flow was positively correlated with wealth, in most studied sources, although seasonality has not been a factor that has significantly changed the diversity and evenness. The trophic composition in all rivers sampled was very similar showing lot of collectors-individuals scavengers and predators.